PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Situmorang, Christina Verawaty; Simanjuntak, Arthur (Universitas Medan Area, 2019)
This study aims to examine and analyze the influence of good corporate governance on corporate financial performance. Good corporate governance in this study is proxied by percentage of institutional ownership, composition of board of directors and composition of independent commissioner. The financial performance of a banking company is measured by Return on Equity (ROE). The population of this study are banking companies Book II and III listed on the Indonesia Stock Exchange (BEI), amounting to 29 companies. The technique of the sample using purposive sampling obtained 19 companies. The type of data used is secondary data. Data analysis technique in this research use multiple linear regression analysis. The results of this study partially indicate that the percentage of institutional ownership, composition of board of directors and composition of independent commissioner has no significant effect with the direction of negative coefficient on ROE. While the simultaneous percentage of institutional ownership, the composition of the board of directors and the composition of independent commissioners composition have significant effect on ROE with positive coefficient direction.